The Effect of KCl Fertilizer and Humic Acid to The Growth and Yields Of Spring Onion (Allium fistulosum L.) - Kartini, Ade Nunu; Riantini, Elin; Wijaya (Ann Publisher, 2024)
The decrease in nutrients in the soil occurs due to leaching, which causes a reduction in the growth and quality of plant yields. Using KCl fertilizer and humic acid is one of the efforts to increase nutrients in the soil and plant growth and yield. This research was conducted in Seda Village, Mandirancan District, Kuningan Regency, from June to August 2024. The research method used was an experimental method with a complete randomized design (CRD), consisting of 16 treatments repeated 2 times. The observed variables consisted of the number of leaves, plant height, number of tillers, root volume, dry weight per cluster, relative growth rate, and fresh weight per cluster. The results of this study showed that the use of KCl fertilizer at a dose of 1.2 g/plant and 0 g/plant humic acid gave good growth and yield in spring onion plants.